Patient satisfaction with waiting time for outpatient prescription services based on sharia characteristics in the pharmacy installation Prof. Dr. Soerojo Hospital Magelang - Arifin Santoso; Ishak; Novia Wulandari (Universitas Muhammadiyah Malang, 2023)
Including pharmaceutical services, service quality improvement must be carried out appropriately, quickly, and with a sense of security. Hospital pharmacy services can be evaluated based on five criteria, namely reliability, responsiveness, assurance, dependability, and empathy. One of the pharmaceutical service factors that must meet the minimum requirements for hospital services is the waiting time for prescription filling. 1) Objective: to assess satisfaction of the duration of the outpatient prescription service wait based on sharia characteristics in RSJ. Prof. Dr. Soerojo Magelang; 2) Methods: descriptively with a cross-sectional design using accidental sampling techniques on questionnaires that were analyzed univariately and bivariately using SPSS; 3) Results: a questionnaire with a total of 30 respondents showed that the patient satisfaction category was very satisfied from the five measurement dimensions (77%, 57%, 73%, 67%, 54%) and satisfied (23%, 43%, 27%, 33% , 46%) with a prescription service wait time not more than 30 minutes for non-concoction and less than 60 minutes for concoction; 4) Conclusion: based on sharia characteristics of the five dimensions of satisfaction, the results are very satisfied and satisfied and the outpatient prescription waiting time service meets the minimum standards of hospital services.